TEACHING PRESENT PROGRESSIVE TENSE THROUGH WHOLE BRAIN METHOD TO THE EIGHT GRADE STUDENTS OF SMP NEGERI 3 PALU - ismi ismi; Nurdin; Ana Kuliahana (Datokarama English Education Journal, 2021)
This research aims to determine whether students’ present progressive can be improved by using the Whole Brain Method. The participants were 20 eight grade students. The researcher had carried out research during the pandemic; the number of students was limited by the school. The research employed true experimental and need pre-test and post-test to both experimental class and control class. The population of this research is students in the grade VIII students of SMP Negeri Palu. The sample was selected by using random sampling technique. The samples are 20 students of class VIII A as the experiment class and VIII C as a control class. The research analyzed the data statistically data collection. The result of data analysis shows that the experimental class (85.5) is higher than the mean score of the control class (69). The deviation score of experimental class (17.64) is higher than of the control class (9.73). The result of t-counted (3.739) is higher than t-table (2.262). In analyzing the data, the researcher used 0.05 level of significance and the degree of freedom (df=10-2) it means that the hypothesis of the research was accepted. Therefore, the Whole Brain Method increase students’ present progressive.